Kinetic properties of the two‐dimensional conducting system formed by CrSi2 nanocrystallites in plane (111) of silicon. Issue 3 (18th October 2013) - Andrievskii, V. V.; Komnik, Yu. F.; Berkutov, I. B.; Mirzoiev, I. G.; Galkin, N. G.; Goroshko, D. L.
<x xml:space="preserve">Abstract</x> The behaviors of resistance, magnetoresistance (up to 5 T), and Hall electromotive force (EMF) with varying temperature (10–300 K) and measuring current (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4swhhqw1" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />10μ</alternatives>A–10 mA) are studied for the Si sample with CrSi2 nanocrystallites (NC) in the plane (111). The conduction in such heterostructure proceeds in the plane with the NC and is the conduction of a two‐dimensional system of charge carriers that shows some unusual effects. The temperature variation of resistivity may be treated as the result of the effect of thermal activation but in this case it is characterized by a low activation energy different in value in different temperature ranges. This suggests that the mechanism of conduction is more complex. It is found that the conduction is determined by the effect of temperature variation not only on carrier concentration but also on its mobility. Magnetoresistivity is also of different shape in different temperature ranges. All the above features are treated in terms of the proposed model of electron hopping through the conduction band (or hole hopping through the valence band). A peculiar effect of giant reduction in resistivity with increasing the measuring current has been revealed. Discussed are some possible factors responsible for this effect.